2004
DOI: 10.3171/jns.2004.101.3.0499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperbaric oxygen therapy on cerebral oxygenation and mitochondrial function following moderate lateral fluid-percussion injury in rats

Abstract: Analysis of data in the current study demonstrates that HBO significantly increases brain tissue PO2 after injury. Nonetheless, treatment with HBO was insufficient to overcome injury-induced reductions in mitochondrial redox potential at 1 hour postinjury but was able to restore redox potential by 4 hours postinjury. Furthermore, HBO induced an increase in VO2 in both injured and sham-injured animals. Taken together, these data demonstrate that mitochondrial function is depressed by injury and that the recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 36 publications
2
70
0
1
Order By: Relevance
“…These mechanisms have been demonstrated in both experimental and clinical investigations and include improved oxidative metabolism and mitochondrial function and reductions in intracranial hypertension, apoptosis, neuroinflammation, and free radical-mediated damage. 9,38,39,41,[44][45][46]50,52,[58][59][60][61]65 The results of the present randomized clinical trial help to support these findings.…”
Section: Mechanism Of Hbosupporting
confidence: 77%
See 2 more Smart Citations
“…These mechanisms have been demonstrated in both experimental and clinical investigations and include improved oxidative metabolism and mitochondrial function and reductions in intracranial hypertension, apoptosis, neuroinflammation, and free radical-mediated damage. 9,38,39,41,[44][45][46]50,52,[58][59][60][61]65 The results of the present randomized clinical trial help to support these findings.…”
Section: Mechanism Of Hbosupporting
confidence: 77%
“…Experimental investigations also support the concept of using HBO 2 followed by continued increased O 2 at normobaric pressures as a single treatment. 9 Daugherty et al, 9 in a lateral fluid percussion TBI rat model with 1 hour of HBO 2 treatment at 1.5 ATA followed by 3 hours of NBH, have documented significant improvement in mitochondrial function as measured by redox potential at the completion of the 4 hours of treatment but not at completion of 1 hour of HBO 2 . These data indicate that mitochondrial function is depressed after TBI but there is a potential for mitochondrial functional recovery and that the combination of HBO 2 and NBH can enhance this recovery.…”
Section: Mechanism Of Hbomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a mouse model with an intrinsic impairment of mitochondrial complex IV, HBOT at 2 atmospheres (atm) "significantly ameliorate[d] mitochondrial dysfunction" and delayed the onset of motor neuron disease when compared to control mice [108] . In animal studies, HBOT has been shown to increase the amount of work done by mitochondria [110] , improve mitochondrial function after brain injury [109] , and prevent mitochondrial deterioration [111] when compared to room air pressure and oxygen levels. HBOT also increased sperm motility by augmenting mitochondrial oxidative phosphorylation in fructolysis-inhibited sperm cells.…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%
“…Since only approximately 0.3% of inhaled oxygen is ultimately delivered to mitochondria [107] , increasing the oxygen delivery to mitochondria by hyperbaric oxygen therapy (HBOT) may actually improve mitochondrial function [108,109] . For example, in a mouse model with an intrinsic impairment of mitochondrial complex IV, HBOT at 2 atmospheres (atm) "significantly ameliorate[d] mitochondrial dysfunction" and delayed the onset of motor neuron disease when compared to control mice [108] .…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%